2006
DOI: 10.1002/meet.14504301181
|View full text |Cite
|
Sign up to set email alerts
|

The role of community‐based, problem‐centered information intermediaries in local problem solving

Abstract: Problem-Centered Information Intermediaries 2 AbstractLobbying for school reform, cleaning up graffiti, installing traffic calming measures, and enacting noise ordinances are daily problem-based activities performed by organized citizen groups. These civic organizations -nonprofit associations, community groups, and neighborhood block watch programs -have operated within communities as a way for people to affect their community's quality of life. Routinely in the course of problem-solving, these organizations-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have discussed the importance of meaningful information formats (Duncombe & Heeks, ; Gomez et al, 2012), and the intermediary role in interpreting, distilling, and reframing information (Durrance et al, ). Our findings evidence issues of comprehension, and provide insight into constructive information intermediary behaviors, and in particular, the incremental and recursive nature of information cycles, and the personalized nature of meaningful information formats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have discussed the importance of meaningful information formats (Duncombe & Heeks, ; Gomez et al, 2012), and the intermediary role in interpreting, distilling, and reframing information (Durrance et al, ). Our findings evidence issues of comprehension, and provide insight into constructive information intermediary behaviors, and in particular, the incremental and recursive nature of information cycles, and the personalized nature of meaningful information formats.…”
Section: Discussionmentioning
confidence: 99%
“…Durrance, Walker, Souden, and Fisher (), investigating everyday information behaviors in a community setting within a US city zone of multiple deprivations, reports that members of local community groups provide an important intermediary role “critical to the information landscape of communities” (2006, p. 2). In particular, they variously: collect and share information and links within and across groups; “routinely… interpret, distill, and re‐frame information” to make it more relevant and accessible to constituents (2006, p. 2); and prepare information for targeted dissemination and use.…”
Section: Introductionmentioning
confidence: 99%
“…Agada (1999) investigated the "information use environments," of residents of an African-American inner-city neighborhood and found that gatekeepers were those individuals within the community who were able to move between cultures and link their communities with resources, and who were perceived as trustworthy and credible sources of information. Durrance et al (2006) examined everyday information behaviors for local community-based citizen's groups in the USA and found that they play an important gatekeeping role because they make information more relevant for their constituents by distilling, tailoring and vetting the information according to the residents' needs. Schilderman (2002) reported on the role that intermediaries have as sources of information for the urban poor in Sri Lanka, Peru and Zimbabwe who prefer gatekeepers from social networks based on kinship, proximity or friendship rather than institutional gatekeepers (government agencies, NGOs and health organizations) who might be better informed but who have been unsuccessful in providing the urban poor with information in personalized formatsand in perceiving the urban poor as partners who are an important source of indigenous knowledge.…”
Section: The Information Role Of Intermediaries For Marginalized Groupsmentioning
confidence: 99%
“…At the same time, nonprofit organizations can be notoriously possessive of their field of work. This has been identified as a barrier to information flow within the sector (Durrance et al , 2006b). This is not always the case, but it requires a delicate approach when navigating community stakeholder networks.…”
Section: The Youth Internship Program: An Ideal Format For Information Literacy Instructionmentioning
confidence: 99%